Avaliação do efeito da frutose-1,6-bisfosfato na prevenção da fibrose pulmonar experimental - Dias, Henrique Bregolin (2019)
Pulmonary fibrosis (PF) is the result of chronic injury where fibroblasts become activated and secrete large amounts of extracellular matrix (ECM), leading to impaired ECM degradation followed by tissue stiffness, loss of lung function and death. Fructose-1,6-bisphosphate is a metabolite from glycolytic pathway that has been studied for many years and showing beneficial actions in different cell lines and tissues. In a recent study from our laboratory, FBP was able to prevent the development of FP bleomycin (BLM)-induced on mice, but the underlying mechanism is still unknown. In this way, the objective of this study was to evaluate the effects of FBP under prevention and regulation of fibrotic process in PF mouse model and lung fibroblasts. In this way, we treated mice that received BLM intratracheally with FBP for 14 days. We also extracted lung fibroblasts and myofibroblasts from healthy and fibrotic animals, respectively. We analyzed lung function, gene expression of collagen subtypes and other important components of ECM, as well proliferation, contraction and migration rates, and proteins involved in ECM degradation. In PF mice model, lung function was improved by FBP as revealed by reduced collagen deposition and downregulation of ECM gene expression such as collagens and fibronectin. Myofibroblasts treated with FBP for 3 days in vitro showed decreased proliferation, contraction, and migration, which are characteristic of myofibroblast to fibroblast phenotype reversal. ECM-related genes and proteins such as collagens, fibronectin and α-smooth muscle actin, were downregulated in FBP-treated myofibroblasts in vitro. Moreover, MMP1, responsible for ECM degradation, and TIMP-1, a MMP1 inhibitor, were up and down regulated, respectively. MMP2, which is associated with fibroblast invasion on tissue, also was downregulated. These results demonstrate that FBP may prevent bleomycininduced PF development through reduced expression of collagen and other ECM components mediated by a reduced TIMP-1 and increased MMP1 production, which would allow a better ECM degradation.